(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The impact of the Internet of Things on transportation will be significant. Automated vehicles (AVs) are designed to make regular activities easier, such as shipping, vehicle traffic, and freight transit. A broad variety of applications are served by AVs, which can even be airborne or underwater in addition to being transport vehicles. An assortment of AVs makeup the Internet of Transportation, a subset of IoT systems. In addition to managing a lot of sensor data, these IoT devices send a lot of sensor data to the cloud for processing. Although AVs have great promise and can dramatically enhance transportation, worries about safety and confidentiality there will be new issues that need to be resolved. In order for these IoT systems to effectively control AVs, AI-based approaches are becoming increasingly important. For virtualized Network of Things devices, this article tackles access control and AI.